2011
DOI: 10.1002/mds.23890
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant supplementary motor complex and limbic activity during motor preparation in motor conversion disorder

Abstract: Background Conversion disorder is characterized by unexplained neurological symptoms presumed related to psychological issues. The main hypotheses to explain conversion paralysis, characterized by a lack of movement, include impairments in either motor intention or disruption of motor execution, and further, that hyperactive self-monitoring, limbic processing or top-down regulation from higher order frontal regions may interfere with motor execution. We have recently shown that conversion disorder with positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
179
0
8

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 195 publications
(204 citation statements)
references
References 40 publications
17
179
0
8
Order By: Relevance
“…Similar evidence has been gathered in recent studies [101][102][103] concerning patients with psychogenic movement disorders such as tremor or dystonia (i.e., positive rather negative motor symptoms), although pointing to the role of different circuits connecting the amygdala to SMA (see also review by Voon et al in this issue). Future research should use more advanced connectivity measures such as dynamic causal modelling (DCM) and compare different conversion patient groups during different symptomatic conditions (pre-vs. post-recovery) to gain better insights into such interactions between motor control and emotion/motivation systems.…”
Section: Figuresupporting
confidence: 84%
See 1 more Smart Citation
“…Similar evidence has been gathered in recent studies [101][102][103] concerning patients with psychogenic movement disorders such as tremor or dystonia (i.e., positive rather negative motor symptoms), although pointing to the role of different circuits connecting the amygdala to SMA (see also review by Voon et al in this issue). Future research should use more advanced connectivity measures such as dynamic causal modelling (DCM) and compare different conversion patient groups during different symptomatic conditions (pre-vs. post-recovery) to gain better insights into such interactions between motor control and emotion/motivation systems.…”
Section: Figuresupporting
confidence: 84%
“…On the other hand, however, unlike the classic view, conversion and hypnosis appear to act on behavior and perception via partly distinct brain circuits. In conversion, modulations of motor and sensory awareness might primarily be driven by an increased recruitment of regions in VMPFC, implicated in the access to self-relevant affective representations and memories [17,104,105,107], as well as other subcortical limbic regions such as the amygdala [45,79,101,102]. These areas might influence movement, sensation, and self-awareness more broadly by promoting or suppressing certain patterns of behaviors through modulatory inputs to motor or sensory pathways (as observed for more primitive adaptive reactions to threat, see [47,104,110]), and/or by imbuing behavior with particular affective and self-relevant associations though an integration of sensorimotor activity with internal representations retrieved from memory or imagery.…”
Section: Discussionmentioning
confidence: 99%
“…Viewing unpleasant images might lead to an overestimation of threat and self-relevance, possibly through retrieved episodic memories linked to negative life events (Brown, 2004). Increased PCC activity was also observed in patients with functional tremor by Voon et al (2011), who concluded that patients may aberrantly assign "stimuli, states or memories as selfrelevant or salient". Similarly, Cojan et al (2009) found greater PCC activity during motor preparation in a patient with functional paralysis, thought to reflect abnormal self-referential processes that may alter subjective motor agency.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a subgroup of patients suffering from conversion tremor presented less connectivity between the supplementary motor area and the bilateral dlPFC (Voon et al, 2011). A decreased activation in parietal areas has been found as well as poorer connectivity between parietal cortex, limbic areas and sensorimotor cortex (Hallett, 2010).…”
Section: Positive Motor Conversion Symptoms: Tremor Aberrant Posturementioning
confidence: 90%
“…Voon proposed for this type of conversion symptoms a theory according to which conversion motor representations previously mapped could trigger, in an alertness context, the voluntary action selection system which would be hypoactive and functionally disconnected from regulatory prefrontal top-down mechanisms (Voon et al, 2011). In this sense, a failure on high-order prefrontal regulation of motor control has been postulated.…”
Section: Positive Motor Conversion Symptoms: Tremor Aberrant Posturementioning
confidence: 99%